2006
DOI: 10.1111/j.1600-6143.2006.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Multicenter Trial of Tacrolimus-Based Therapy with or without Basiliximab in Pediatric Renal Transplantation

Abstract: In a 6-month, multicenter, randomized, controlled, open-label, parallel-group trial, we investigated the efficacy and safety of adding basiliximab to a standard tacrolimus-based regimen in pediatric renal transplant recipients. Patients <18 years received tacrolimus/azathioprine/steroids (TAS, n = 93) or tacrolimus/azathioprine/steroids/basiliximab (TAS + B, n = 99). Target tacrolimus levels were 10-20 ng/mL between days 0-21 and 5-15 ng/mL thereafter. Steroid dosing was identical in both groups. Basiliximab w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 24 publications
4
107
1
Order By: Relevance
“…In all three studies, 73,75,77 it was not clear whether or not all reported outcomes were the same as those in the trial protocol and the reporting of loss to follow-up, withdrawals and dropouts was also not clearly reported.…”
Section: Completeness Of Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…In all three studies, 73,75,77 it was not clear whether or not all reported outcomes were the same as those in the trial protocol and the reporting of loss to follow-up, withdrawals and dropouts was also not clearly reported.…”
Section: Completeness Of Trialsmentioning
confidence: 99%
“…In summary, three RCTs (published in seven papers [73][74][75][76][77][78][79] and one abstract 72 ) were found eligible and are included in this review (Table 10). • Abstract, n = 332…”
Section: Randomised Control Trialsmentioning
confidence: 99%
See 3 more Smart Citations